Implementasi Restrukturisasi Pembiayaan Selama Masa PPKM di Bank Syariah Indonesia Kc Gatot Subroto Kota Jambi - Sissah Sissah; Ahsan Putra Hafiz; Bimbi Agnesia Putri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Mudharabah financing is used by MSME customers and non-MSME customers in Sharia banking practices because there is minimal risk for both the Sharia bank and the customer. However, the PPKM pandemic is sweeping the world so many people are affected, one of which is MSME customers, which has an impact on the performance and ability to pay MSME customers' obligations to banks. The aim of the research is to analyze the implementation of financing restructuring during the PPKM period and to analyze the supporting and inhibiting factors in implementing financing restructuring during the PPKM period at Bank Syariah Indonesia KC Gatot Subroto, Jambi City. Restructuring has been implemented since the inception of Bank Syariah Indonesia (BSI). The supporting factors in the implementation of restructuring at Bank Syariah Indonesia (BSI) are internal factors originating from the bank and external factors originating from the customer, while inhibiting factors in its implementation are the lack of openness or dishonesty of customers towards the bank when asked for information, lack of communication when want to be asked for information or lack of transparency, and lack of personnel or staff who understand well the implementation of restructuring. Bank Syariah Indonesia (BSI) is expected to be more careful and more selective in analyzing the provision of financing so that it will minimize the occurrence of problematic financing in the future and the analysis that must be carried out by Bank Syariah Indonesia (BSI) in carrying out restructuring is expected to be guided by the bank's regulations and rules. established sharia rules.